Preventive effects of pneumococcal and influenza vaccines on community-acquired pneumonia in older individuals in Japan: a case-control study - Kanzo Suzuki; Kyoko Kondo; Masakazu Washio; Kei Nakashima; Sakae Kan; Seiichiro Imai; Kunihiko Yoshimura; Chiharu Ota; Satoko Ohfuji; Wakaba Fukushima; Yoshio Hirota (Taylor & Francis Group, 2019)
At present, there are few reports that have clarified the effectiveness of 23-valent pneumococcal polysaccharide vaccine (PPSV23) against all-cause pneumonia or pneumococcal pneumonia in community-acquired pneumonia (CAP) in older individuals in Japan. We conducted a hospital-based matched case-control study to investigate separately the preventive effects of PPSV23 and trivalent influenza vaccine (TIV) on all-cause CAP and pneumococcal CAP in older individuals in Japan. Cases were individuals aged 65 years or older who were newly diagnosed with CAP from October 2010 to September 2014. Two control patients with a different disease (one respiratory medicine and one non-respiratory medicine) matched for sex, age, date of outpatient visit, and medical institution were selected for each case. Odds ratios (ORs) and 95% confidence intervals (CIs) of PPSV23 and TIV for the occurrence of all-cause CAP and pneumococcal CAP were calculated using conditional and unconditional logistic regression models. The analysis included 161 cases and 308 controls from the 4-year period. The adjusted OR for the occurrence of all-cause CAP was 0.76 (95%CI = 0.44-1.32) with PPSV23 vaccination and 0.79 (95%CI = 0.50-1.25) with TIV vaccination compared with unvaccinated individuals. When the outcome index was restricted to pneumococcal CAP, the adjusted OR significantly decreased to 0.23 (95%CI = 0.08-0.66) with PPSV23 vaccination, but not with TIV vaccination (adjusted OR = 0.65, 95%CI = 0.31-1.36). PPSV23 vaccination is likely effective in reducing incidence of pneumococcal CAP in older individuals, although its preventive effect for all-cause CAP has not been achieved.